Heritage, sacredness and power: on different categories of historical and cultural patrimony in Brazil - Aline Sapiezinskas Krás Borges Canani; Michele Andrea Markowitz (Horizontes Antropológicos)
This article deals with the concept of heritage present in the public policies of cultural, artistic and historical heritage preservation, aiming to widen the apprehension of the concept. Bringing examples from my fieldwork in Venezianos Lane, in Porto Alegre, my purpose in this article is to analise the attribution of values to specific buildings, objects or processes as a way to produce new meanings within the different contexts in which it occurs, observing specially the construction of signification from the point of view of familiar heritage, heritage objects seen as sacred properties and the dimension of power involved in such process. Considering the ressignifications which resulted from the heritage acknoledgement, I analise the different categories perceived by the city inhabitants who are involved with the heritage, not in a passive way, but owning the capacity to construct new significances and to give meaning to the world around them. I try to underline the symbolic dimension present in this process in which the property acquires a meaning and comes to be considered heritage.